Effectiveness of an Interventional Program on Nursing Staff’ Knowledge Concerning Prevention of Pressure Ulcer at the Intensive Care Unit in Al-Diwaniyah Teaching Hospital - Ali M. Noor; Hakima Shaker Hassan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective (s): This study aims to evaluate the effectiveness of an interventional program on nursing staff’knowledge concerning prevention of pressure ulcer at the intensive care unit in Al-Diwaniyah TeachingHospital, and to find out the relationships between nurse’s knowledge and their socio-demographiccharacteristics (age, gender, level of education, years of experience in intensive care unit, and participationin training session).Methodology: A pre-experimental design (one group of sample) used to guide this study, it was conductedby use of a pre-posttest approach during the period October 5th 2020, to March 20th 2021. A non-probability(purposive) sampling has been performed during a selection of (27) nurses who works at the intensive careunit in Al-Diwaniyah Teaching Hospital were exposed to the interventional program. In order to reachthe aims of the study, the researcher constructed program and questionnaire format to assess the nurses`knowledge, the questionnaire format was consisted of (4) domains; composed as a total of (24) questionsregarding pressure ulcer prevention. The validity of the program and instrument was determined bypresenting it to (15) specialist experts and reliability of the instruments was determined through (test-retest)approach for knowledge test. The data analyzed through the use of a descriptive and inferential statistical inorder to discover the differences between the pre and post implementation.Result: The findings of the current study revealed that there are highly statistically significant differences inposttest in the study sample in all knowledge domains at P equal 0.001. The findings also show that there isa statistical association between nurses` knowledge and their educational level and participation in trainingsessions regarding pressure ulcer prevention.Conclusion: The study concluded that the effectiveness of an interventional program on nurses’ knowledgeregarding pressure ulcer prevention is positive at a high rate.